HETEROSIS, COMBINING ABILITY AND GENE ACTION ESTIMATIO IN PEA (Pisum sativa L.) USING FULL DIALLEL CROSSES - & et al., Askandar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out at the experimental field, College of Agriculture, University of Duhok, during 2013- 2015, using six genotypes of pea. The objective of this experiment to investigate heterosis and several genetic parameters by using full diallel cross. The results revealed that general combining ability were significant in all studied traits except No. of grain pod-1, also special combining ability and reciprocal were significant in all traits at probability 5%.